Challenges to Romanian Higher Education - Agachi, Paul (International Higher Education, 2012)
Romania faces serious academic challenges, particularly in the context of current economic problems in Europe. Further, the traditional of centralized control and hierarchy remains. At the same time, several Romanian universities are instituting reforms that are improving them.